Ultrastructural Aspects of Spermatogenesis in Phalloceros caudimaculatus (Teleostei, Poeciliidae) - Vicentini, Carlos Alberto [UNESP] (2010)
The aim of the present study was to analyze the ultrastructural aspects of spermatogenesis in Phalloceros caudimaculatus, during cell proliferation. The parenchyma is organized morphologically as lobular restricted spermatogonial testis. Spermiogenesis in this species is characterized by four morphological stages of development (spermatids S1 through S4). The mature spermatids and spermatozoa heads are situated at the periphery of the cyst surrounded by the cytoplasm of the Sertoli cells. The germ cell's ultrastructure and spermatogenesis in P. caudimaculatus are very similar to that of other poeciliids.